Ritual and myth in native American fiction - Klečková, Magdalena (Univerzita Pardubice, 2009)
This diploma thesis is focused on the presence of native American myths and rituals in literature. It uses the novels Ceremony, House made of dawn and love medicine to demonstrate the function and importance of rituals and myths in the chosen texts. The use of native American elements is explored on the background of the authors, their tribes and mythologies. The investigation of storytelling tradition is aimed at showing and relating written literature to the native oral world.
Rituály a mytologie v literatuře amerických indiánů
Keywords: Silko; Erdrich; Momaday; Indiáni; američtí indiáni; Chippewa; Silko; Erdrich; Momaday; Indians; Native Americans; Chippewa